Integrated Financial Supervision: an Institutional Perspective for the Philippines - Melanie S. Milo (Philippine Institute for Development Studies (PIDS), 2007)
This paper looks at the issue of reforming financial regulatory structures from the New Institutional Economics perspective. In particular, it examines how the broader institutional environment prevailing in developing countries like the Philippines may affect the institutional arrangements for financial regulation, and how these might be taken into consideration when designing or reforming financial regulatory structures. The paper argues that the state of financial conglomerates in the Philippines does not warrant a shift toward integrated financial supervision. Instead, any effort to reform the financial supervisory structure must explicitly address the countrys most fundamental need, which is to strengthen institutions and governance structures. Key institutional characteristics must already be in place to undertake such a reform successfully, including sound political and legal systems and enforcement mechanisms. That being said, properly structured independent regulatory agencies in the financial sector can play a part in strengthening the overall regulatory environment.
Keywords: 330; financial sector; regulatory structure; financial development; financial services regulation; regulatory agencies; integrated supervision; institutions; Finanzsektor; Konglomerat; Bankenaufsicht; Neue Institutionenökonomik; Philippinen